AN ANALYSIS OF THE BUSINESS FEASIBILITY OF PONTIANAK'S BINGKE CAKE IN BANDUNG CITY - Rizka Natasya Dwitiandi; Ridlwan Muttaqin; Widyastuti Nurmalia Utami (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study examines the feasibility of expanding the Pontianak traditional delicacy—bingke cake—to Bandung City. Employing a mixed-methods approach (qualitative and quantitative), it evaluates market dynamics, human resource requirements, and financial viability. Data were collected through interviews, observations, and documentary studies. Financial feasibility was analyzed using the Break-Even Point (BEP) method, while strategic readiness was assessed via SWOT analysis. The results indicate that sales volume in recent months has consistently exceeded the break-even point, signifying financial viability for expansion. The SWOT analysis revealed strengths in cultural appeal and market potential within Bandung, but also identified challenges such as limited production capacity and human resources. The study concludes that the bingke cake business is feasible for expansion and provides strategic recommendations, including workforce development and local marketing strategy adjustments. These findings contribute to entrepreneurship literature and offer practical guidance for MSMEs in developing traditional culinary businesses in urban markets.